Experimental and numerical characterization of sub-zero phase change materials for cold thermal energy storage - Borri, Emiliano (2022)
Latent heat thermal energy storage systems are gaining increasing attention due to their high energy density and ability to discharge at near isothermal temperatures. A good understanding of the thermal behaviour of phase change materials (PCMs) used in these systems and therefore, a methodology for the characterisation of the phase change behaviour of storage media during charge and discharge phases is important for an optimised storage design. In this work, an experimental rig in a cylindrical shape container was designed to obtain the thermal profiles of different category of sub-zero PCMs. The experimental measurement of deionised water (ice) was first used to calibrate and validate a numerical 1-D model. Three types of sub-zero PCMs were further tested including aqueous sodium chloride, aqueous ethylene glycol and decane. The numerical results showed that aqueous alcohol had the best agreement with the experiments. In the case of paraffin and aqueous sodium chloride, a discrepancy between numerical and experimental results was found. In particular, during the melting phase, the discrepancy was due to the effect of natural convection while, during the solidification phase, it was due to the effect of supercooling. This highlights the importance of correct estimation of those effects for an accurate prediction. However, due to its simplicity, the 1-D model can be considered a valid method to approximate behavior of the different PCM and to compare the thermal profiles of different materials.